Faktor Pemungkin Terkait Perilaku Ibu Memberikan Asi Eksklusif 6 Bulan di Wilayah Kerja Puskesmas Kemiri Muka Kota Depok Tahun 2011 - Ida Ida; Kenti Friskarini (Jurnal Persada Husada Indonesia, 2015)
Breast milk constitutes as the most suitable food for an infant and contains the highest value whencompared to baby food created by man or even animal milk. In Kota Depok in 2010, exclusive breastfeeding tillthe age of 6 months is still low at 61,93%. This article is about the relationship of enabling factors. This studyconstitutes a study with cross-sectional design and survey methods were applied. Location of study was atPuskesmas Kemiri Muka work area. Interviews were carried out using questionaires on on a study population of251 mothers with infants between 6 to 12 months of age, of which 172 mothers were samples. Study resultsshowed that the conferment of 6 months exclusive breastfeeding in the work area of PusKesMas Kemiri KotaKota Depok was still low. Study results revealed only 44 respondents or 25,6% conferred 6 months of exclusivebreastfeedings. The meaningful enabling factors in relation is the Early Breastfeeding Initiation (EBI) andnursing cluster. Recommendation from this study result is the expectation for Kota Depok Health Agency andPusKesMas Kemiri Muka to intensify the application and monitoring towards EBI and nursing clusterimplementations between infant and mother.Key Words: Enabling Factor, Maternal Behaviour, 6 Months Exclusive Breastfeeding